Implementasi Metode-Metode Pembelajaran Dalam Pendidikan Agama Islam (PAI) - Arlina A; Mawar Ayuni; Krisna Bayu Pratama; Napita Sapitri Nasution (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to examine the application of Islamic learning methods in the learning process of Islamic Religious Education  (PAI) learning process delivered by lecturers. This research uses a descriptive qualitative approach with case study method. The research subjects were Islamic Education lecturers, while the data were collected through observation, and documentation techniques. TThe results showed that PAI lecturers applied various learning methods in a varied manner varied. They combine several methods in one learning activity to learning activities to complement the shortcomings of each method, so that learning process becomes more effective and efficient. The methods used include the method of targhib and tarhib, exemplary, stories, habituation, tamtsil, ibrah with i'tibar, and reward and punishment.